Edukasi Beyond Used Date (BUD) Obat di Kelurahan Gagak Sipat, Ngemplak, Boyolali - Fitri Kurniasari; Jena Hayu Widyasti; Ismi Puspitasari; Carolina Eka Waty (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
Community service with the theme of Expired Date (ED) and Beyond Use Date (BUD) aims to improve knowledge and understanding of proper medication storage as an effort to enhance the health of the Gagak Sipat community. Knowledge about medication usage limits and checking product expiration dates educates the public to be more cautious and to avoid health risks that may arise from consuming products that have exceeded their usage period or have expired. The use of medicines beyond their ED and BUD indicates that the drugs may have experienced reduced stability related to storage conditions. Decreased stability of pharmaceutical preparations can affect their physical quality, which in turn impacts the effectiveness and safety of the medication. The educational method used in this program included lectures accompanied by the distribution of leaflets, followed by practical simulations on checking ED and calculating BUD for various dosage forms. The results of this educational activity showed that community members were able to determine the ED and BUD for several pharmaceutical preparations such as tablets, powders, capsules, syrups, eye drops, ear drops, and others. The community in Gagak Sipat village gained an understanding of the risks associated with using medications beyond the BUD, including reduced effectiveness, the risk of microbial contamination, and potentially harmful chemical reactions. It was emphasized that some medications that are expired or used beyond their BUD can pose more serious health risks, especially when used to treat severe diseases.